The The Influence of Service Quality, Prices, and Promotions on the Satisfaction of Pilgrims on Hajj and Umrah Destinations at the Hajj and Umrah Travel Agency PT. Pandi Kencana Murni - Ruslan, Andika; Moelyati, Trisniarty Adjeng; Choiriyah, choriyah (International Journal of Marketing & Human Resource Research, 2024)
This research aims to determine the influence of Service Quality, Price, and Promotion on Umrah Pilgrim Satisfaction at the Hajj and Umrah Travel Bureau PT. Pandi Kencana Murni (Pakem Tours). The sampling technique in this research used the Cluster Sampling technique by taking samples from representatives of the Pakem Tours Palembang, Jakarta, and Makassar branch offices as many as 198 people. The research method used is associative research using primary data obtained from the results of questionnaire answers. The analysis technique used is Multiple Linear Regression. This research shows that simultaneously, there is a positive and significant influence of Service Quality, Price, and Promotion on the Satisfaction of Umrah Pilgrims at the Hajj and Umrah Travel Bureau PT. Pandi Kencana Murni (Pakem Tours). Partial testing shows a positive and significant influence of Service Quality and Price on Congregation Satisfaction at the Hajj and Umrah Travel Bureau PT. Pandi Kencana Murni (Pakem Tours). Partially there is a positive and insignificant effect and no effect of Promotion on Umrah Pilgrim Satisfaction at the Hajj and Umrah Travel Bureau PT. Pandi Kencana Murni (Pakem Tours).